Pengembangan Media Promosi Lembaga Pendidikan Menggunakan Papan Informasi Digital di MAN 1 Padangsidimpuan - Yuli; Supriadi, Supriadi; Musril, Hari Antoni; Okra, Riri (ANTHOR: Education and Learning Journal, 2023)
This research is motivated by the fact that in MAN 1 Padangsidimpuan, various information related to the school is still delivered in a simple way using two-dimensional media such as banners, posters, announcement papers, and brochures affixed to the making or delivered via microphone. This makes some students less informed with the media used can be damaged, and lost. The purpose of this study, among others, is to make it easier for students to get information, and make it easier for teachers to convey information to be conveyed. The research method used in this research is a research and development method known as Research And Development (R&D) The development model used by Waterfall Pressmanconsists of 5 stages, namely communication, Planning, Modeling, Construction, and Deployment. The research was tested through three stages, namely the validity test was carried out with several experts in their fields such as content, construct, and language using Aiken's V formula. Second, the practicality test was carried out with teachers at the research location using the Moment Kappa (k) formula, and the effectiveness test was carried out with several students using the G-Score formula (<g>). The results of research on media promotion of educational institutions that can be used by schools. The form of this media is a website-based digital information board. The validity product test was 0.88 which was declared valid, the practicality test result of 0.93 was declared very practical, and the effectiveness test result of 0.94 was declared effective. So it can be concluded that the promotional media for educational institutions using digital information boards are valid, practical, and effective.